ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN ASURANSI DI PASAR MODAL INDONESIA - Akhyar, Muhammad Fariz; Indraswati, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to investigate the factors that influence the profitability of insurance companies listed on the Indonesian capital market, with a focus on leverage (proxied as debt to equity ratio), risk-based capital, and underwriting results. The data used covers the period 2018 to 2022, and takes a sample of ten insurance companies listed on the Indonesia Stock Exchange. The analysis method used is panel data regression with the dependent variable of company profitability and the independent variables of leverage, risk-based capital, and underwriting results. Based on the results of the analysis, it is known that the appropriate model used in the panel data regression analysis of this study is the Random Effect Model (REM). The results showed that underwriting results have a significant effect on profitability. While leverage and risk-based capital have no significant effect on profitability in insurance companies listed on the Indonesia Stock Exchange for the period 2018-2022.